Insights Into Intra-arterial Thrombolysis in the Modern Era of Mechanical Thrombectomy - Castonguay, Alicia C.; Jumaa, Mouhammad A.; Zaidat, Osama O.; Haussen, Diogo C.; Jadhav, Ashutosh; Salahuddin, Hisham; Zaidi, Syed F. (Frontiers in Neurology, 2019)
Background and Purpose: The role of intra-arterial (IA) thrombolysis in modern endovascular therapy is not well understood. Here, we surveyed neurointerventionalists to understand their current clinical practices and opinions of IA thrombolysis in the new era of mechanical thrombectomy (MT). Method: A 24-question anonymous survey was distributed via email to the members of the Society of Vascular and Interventional Neurology. Results: 104 responses were included in the analysis. Most respondents were interventional neurologists (76.9%) and had ≥5-years in neuro-interventional practice(80.8%). IA thrombolytics are presently used by 60.6%. Aspiration plus stent-retriever was the most common MT approach used with IA-thrombolysis (66.0%). IA-thrombolysis was used in mainly three approaches: 1)treatment of primary distal occlusions, 2)as rescue after proximal occlusion thrombectomy, and 3)or as adjunct therapy to primary MT approach. The most frequent IA-rtPA dose was 3-10mg, with 1mg/min infusion rate(56.6%). 84.9% do not have a standardized protocol for administering IA-rtPA. About half(50.9%) believed there should be no time limit for administering IA lytic if there is a favorable imaging profile, while 30.2% indicated ≤6 hours. Most respondents (76.5%) would consider using IA-tenecteplase in a trial setting. Only 12.9% felt there was no role for IA thrombolysis in modern endovascular practice. Respondents with ≥10-years’ experience were less supportive of the future of IA lytic (98.0% versus 76.4%,p=0.006). Conclusion: IA-thrombolysis is currently used in clinical practice; however, there is no clear consensus on best practices or criteria for administration. Further studies are needed to define the role of IA-thrombolysis in the context of MT.